Development of QR code-based interactive ludo learning media for teaching Pancasila values to fourth grade students - Maulindah, Ifa Dewi; Purnama, Arda; Khotimah, Khusnul (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
This study aims to develop a product in the form of an application as a learning medium, namely the Interactive Ludo Learning Media Based on QR Codes for Teaching the Application of Pancasila Values, which is both valid and practical. The research employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The study was conducted at SDN 1 Kedungrejo and SDN 2 Kedungrejo with fourth-grade students as the subjects. Data were collected through observations, interviews, and questionnaires. The instruments used were student response questionnaires and questionnaires assessing student and teacher needs. The results of the validity test of the QR Code-based learning media reached an average score of 92%, categorised as very valid, while the practicality test yielded an average score of 94%, indicating a very practical level. Therefore, it can be concluded that the study successfully developed Interactive Ludo Learning Media Based on QR Codes for the Application of Pancasila values among fourth-grade elementary school students, which met the standards of validity and practicality.